Occurrence Regularity and Mating Rhythm of Overwintering Adults of Tessaratoma papillosa on Longan Tree - Jimin, Liu; Qichun, Huang; Ge, Wei; Zhenglin, Chen; Chaofu, Huang; Chunhui, Wan; Bao, Jia; Ningzu, He; Wen, Lu (Plant Diseases and Pests(植物病虫害研究：英文版), 2013)
[ Objeodve ] The occurrence regularity and mating rhythm of overwintering adults of Tessaratoma papiUosa on longan tree were studied in the paper, so as to provide scientific reference for effective prevention and control against the pest. [Method] During the mating period of overwintering adults of T. papillosa, mating duration, occurrence regularity and mating rhythm of overwintefing adults within g8 h as well as their occurrence and mating status during April and June were observed. [Result] Mating duration of T. pap///osa adults for$ -9 h accounted for 18.2%, and duration for 10 -ll h and more than 13 h accounted for 54.5% and 27.3%, respectively. According to daily observation, the maximum adult quantity of T. papillosa adults appeared at 9：00 am, followed by 13：00 pm. There were two peaks （9：00 am and 15：00 pm） and troughs （6：00 am and 19：00 pro） for adult quantity of T. papiUosa and its mating pairs within 24 h as times changed. Mating pairs were positively correlated with observed adult quantity. Adult quantity and mating pairs increased since April 1, and reached the maximum value on April 6. Afterwards, they were gradually dropped down, and almost no adults of T. papiUosa were found after June 11. [Conclusion] The mating peak of T. papillosa adults was from April to May, and there were two mating peaks （9：00 am and 13：00 pm） and troughs （6：00 am and 19：00 pm） every day. Adults repeatedly mated and spawned, while mating usually lasted for 10 -11 h either during the daytime or at night.